Gut Microbial Metabolite Short-Chain Fatt Acids Partially Reverse Surgery and Anesthesia-Induced Behavior Deficits in C57BL/6J Mice - Xu, Xiaohan; Wang, Kexin; Cao, Xuezhao; Li, Zhe; Zhou, Yongjian; Ren, Jiancong; Liu, Fang (Frontiers in Neuroscience, 2021)
Accumulating evidence has demonstrated that damages of gut microbiota are strongly associated with central nervous system (CNS) diseases, such as perioperative neurocognitive disorders (PND). The present study investigated the role of gut microbial metabolite short-chain fatty acids (SCFAs) in surgery-induced cognitive deficits and neuroinflammation in the hippocampus. Adult male C57BL/6J mice received either SCFA mixture or saline orally for 4 weeks, and then partial hepatectomy was performed. The fecal supernatant of surgical mice was transplanted to normal mice for 3 weeks. The Morris water maze (MWM) and open-field tests were used to evaluate behavioral performance on postoperative or post-transplantation days 3 and 7. In the MWM test, pretreatment with exogenous SCFAs partially reversed surgery-induced impairments in crossing times and the time spent in the target quadrant on postoperative day 3 (p < 0.05, p < 0.05, respectively). In the open-field test, compared with the surgical mice, exogenous SCFA administration prior to surgery partially improved the locomotor activity (p < 0.05) and anxiety-like behavior (p < 0.05) on postoperative day 3. Surgical trauma and anesthesia enhanced ionized calcium-binding adapter molecule 1 (Iba-1) expression (p < 0.001), increased the levels of interleukin (IL)-1β (p < 0.001) and IL-6 (p < 0.001), and inhibited SCFA production (p < 0.001) on postoperative day 3. The expression of the brain-derived neurotrophic factor (BDNF) was also decreased (p < 0.001). Overall, surgical trauma and anesthesia exacerbated cognitive impairment, enhanced neuroinflammatory responses, and inhibited SCFA production. Pretreatment with SCFAs attenuated these effects partially by reversing microglial overactivation, inhibiting neuroinflammatory responses, and enhancing BDNF expression.